2021
DOI: 10.3390/nano11040828
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shear Deformation on C-N Structure under Pressure up to 80 GPa

Abstract: We studythe effect of shear deformation on graphitic g-C3N4 under pressures of up to 80 GPa at room temperature. g-C3N4 samples are transformed from initial amorphous flakes into onion-like structures, in which the nitrogen content in the quenched samples decreases with increasing pressure (from 42% in the initial conditions to 1% at 80 GPa). The concentration of the sp2 bonds also decreases from 1 (the initial sample) to 0.62 with increasing pressure to 80 GPa. This transformation of the sample is due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Various experimental techniques were employed, in particular chemical (CVD) and physical (PVD) vapor depositions, [27] solvothermal methods, [9] and static and dynamic high-pressure methods. [3,7,8,10,13,15,17,28,29] In spite of these extensive studies, there is but a single report on the formation of a fully saturated sp 3 -hybridized carbon nitride, namely the CN compound, obtained in a diamond anvil cell laser-heated to 7000 K above 55 GPa. [3] The structure was proposed based on the match of the observed powder diffraction peaks with those of the theoretically predicted 𝛽-InS type CN compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various experimental techniques were employed, in particular chemical (CVD) and physical (PVD) vapor depositions, [27] solvothermal methods, [9] and static and dynamic high-pressure methods. [3,7,8,10,13,15,17,28,29] In spite of these extensive studies, there is but a single report on the formation of a fully saturated sp 3 -hybridized carbon nitride, namely the CN compound, obtained in a diamond anvil cell laser-heated to 7000 K above 55 GPa. [3] The structure was proposed based on the match of the observed powder diffraction peaks with those of the theoretically predicted 𝛽-InS type CN compound.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] These predictions sparked an enormous interest and resulted in numerous experimental and theoretical investigations. [ 3–26 ] It was suggested that the initially considered β‐Si 3 N 4 ‐type C 3 N 4 [ 1 ] is thermodynamically unfavorable compared to other CN compounds. [ 4,23 ] Three possible stoichiometries, CN, C 3 N 4, and CN 2 , were proposed for stable carbon nitrides, all featuring 3D polymeric structures in which C and N atoms are fourfold‐ and threefold‐coordinated, respectively.…”
Section: Introductionmentioning
confidence: 99%